Khan Academy: Strengthening Calculus I Learning in College Students - Salvatierra Melgar, Angel (2021)
Higher Education in Cuba is a particular transformational process; indeed, the development of knowledge in the society requires new demands in the universities. One of this demand is precisely the educational inclusion of young university students, for the achievement of the necessary professional skills in their performances. Particularly, those who have a diagnosis on stuttering and the ones who are studying pedagogical careers, need special attention by a language specialist (speech therapist) so that they can achieve their independence required by the exercise of the profession from a quality education. The speech therapy cabinet office is an excellent place to favor the educational inclusion of young university students with a diagnosis of stuttering, however, there is a limited level of knowledge by teachers, students and managers about the role they play in this regard. This article is aimed at evaluating the work that is done from the speech therapy cabinet of the Central University “Marta Abreu” de Las Villas (Villa Clara province, Cuba), to favor the educational inclusion of a young woman with Stuttering diagnosis. In order to achieve this purpose, an exploratory research was implementedthrough a case study, which constituted the initial phase of a further study. As a result, the diagnosisof the real state of the work that is carried out from the speech therapy cabinet was obtained, in relation to the educational inclusion of a young woman with a diagnosis of stuttering.